Kinin B1R Activation Induces Endoplasmic Reticulum Stress in Primary Hypothalamic Neurons - White, Acacia; Parekh, Rohan Umesh; Theobald, Drew; Pakala, Pranaya; Myers, Ariel Lynn; Van Dross, Rukiyah; Sriramula, Srinivas (Frontiers in Pharmacology, 2022)
The endoplasmic reticulum (ER) is a key organelle involved in homeostatic functions including protein synthesis and transport, and the storage of free calcium. ER stress potentiates neuroinflammation and neurodegeneration and is a key contributor to the pathogenesis of neurogenic hypertension. Recently, we showed that kinin B1 receptor (B1R) activation plays a vital role in modulating neuroinflammation and hypertension. However, whether B1R activation results in the progression and enhancement of ER stress has not yet been studied. In this brief research report, we tested the hypothesis that B1R activation in neurons contributes to unfolded protein response (UPR) and the development of ER stress. To test this hypothesis, we treated primary hypothalamic neuronal cultures with B1R specific agonist Lys-Des-Arg9-Bradykinin (LDABK) and measured the components of UPR and ER stress. Our data show that B1R stimulation via LDABK, induced the upregulation of GRP78, a molecular chaperone of ER stress. B1R stimulation was associated with an increased expression and activation of transmembrane ER stress sensors, ATF6, IRE1α, and PERK, the critical components of UPR. In the presence of overwhelming ER stress, activated ER stress sensors can lead to oxidative stress, autophagy, or apoptosis. To determine whether B1R activation induces apoptosis we measured intracellular Ca2+ and extracellular ATP levels, caspases 3/7 activity, and cell viability. Our data show that LDABK treatment does increase Ca2+ and ATP levels but does not alter caspase activity or cell viability. These findings suggest that B1R activation initiates the UPR and is a key factor in the ER stress pathway.